Novel missense mutations in PTCHD1 alter its plasma membrane subcellular localization and cause intellectual disability and autism spectrum disorder. Issue 7 (3rd May 2021) - Halewa, Judith; Marouillat, Sylviane; Dixneuf, Manon; Thépault, Rose‐Anne; Ung, Dévina C.; Chatron, Nicolas; Gérard, Bénédicte; Ghoumid, Jamal; Lesca, Gaëtan; Till, Marianne; Smol, Thomas; Couque, Nathalie; et al.
Abstract: The X‐linked PTCHD1 gene, encoding a synaptic membrane protein, has been involved in neurodevelopmental disorders with the description of deleterious genomic microdeletions or truncating coding mutations. Missense variants were also identified, however, without any functional evidence supporting their pathogenicity level. We investigated 13 missense variants of PTCHD1, including eight previously described (c.152G>A, p.(Ser51Asn); c.217C>T, p.(Leu73Phe); c.517A>G, p.(Ile173Val); c.542A>C, p.(Lys181Thr); c.583G>A, p.(Val195Ile); c.1076A>G, p.(His359Arg); c.1409C>A, p.(Ala470Asp); c.1436A>G, p.(Glu479Gly)), and five novel ones (c.95C>T, p.(Pro32Leu); c.95C>G, p.(Pro32Arg); c.638A>G, p.(Tyr213Cys); c.898G>C, p.(Gly300Arg); c.928G>C, p.(Ala310Pro)) identified in male patients with intellectual disability (ID) and/or autism spectrum disorder (ASD). Interestingly, several of these variants involve amino acids localized in structural domains such as transmembrane segments. To evaluate their potentially deleterious impact on PTCHD1 protein function, we performed in vitro overexpression experiments of the wild‐type and mutated forms of PTCHD1‐GFP in HEK 293T and in Neuro‐2a cell lines as well as in mouse hippocampal primary neuronal cultures. We found that six variants impaired the expression level of the PTCHD1 protein, and were retained in the endoplasmic reticulum suggesting abnormal protein folding. Our functional analyses thus provided evidence of the pathogenic impact of missense variants in PTCHD1, which reinforces the involvement of the PTCHD1 gene in ID and in ASD. Abstract : Thirteen missense variants in the PTCHD1 gene associated with X‐linked neurodevelopmental disorder were investigated to address their potentially deleterious impact. Their overexpression in various cell lines (HEK293T, Neuro‐2a) and in primary neuronal cultures revealed abnormal protein stability and impaired subcellular localization, thus providing further evidence for the significant impact of PTCHD1 genetic alterations in intellectual disability and in autism spectrum disorder.